STUDY ON THE TOXICITY OF FRESHWATER PUFFERS IN VIETNAM - Ha, Dao Viet (Vietnam Journal of Marine Science and Technology, 2008)
27th May 2004, in Giang Trom district, Ben Tre province, Vietnam, 5 victims (3 died) were poisoned after eating rice soup cooked with freshwater puflers, which were caught from private pond. Before this accident, local people had believed that only marine puffer may be toxic, while freshwater puffer can be eaten safety. The studied results indicated that two species of freshwater puffer, Green-spotted puffer Chelonodon nigroviridis and Red-eyes puffer Carinotetraodon lorteri were collected from Ben Tre and Tra Vinh provinces in 2005 are dangerous for human consumption. The toxin was variety among all of body parts with highest toxicity in liver and reproductive organs (ovary or testis). They are small (5 - 10 g) and may be often eaten without removing hepatopancrea, so it is more potential poisoning Toxin in these two species was identified as tetrodotoxin, the same as Blue-ringed octopus, Horseshoe crab ...